A Dual Delineation Approach to Untangle Interferences in Well Doublets Systems. Issue 5 (10th January 2020) - Sbai, Mohammed Adil
Abstract: Traditional numerical methods for the delineation of wellhead protection areas span deterministic and probabilistic approaches. They provide time‐related capture zones. However, none of the existing approaches identifies the groundwater contribution areas related to each source or sink. In this work, the worthiness of the so‐called double delineation approach was extended. This task was achieved by simple postprocessing of its dual outputs leading to a highly efficient screening tool. In the particular context of geothermal resources management through the well doublets of the Dogger aquifer in the Paris Basin (France), the approach was extended to forecast the compositional heat breakthrough at production wells. Hence, cold‐water breakthrough and temperature decline in production wells are timely assessed in low‐enthalpy geothermal reservoirs. The method quantifies how groundwater volumes are moving through space and time between any couple of source and sink. It provides unprecedented tools advancing the enhanced understanding of water resources systems functioning. It is highly recommended to implement the presented concepts in the current and future generations of community groundwater models. Abstract : Article impact statement : In this work, the worthiness of the dual delineation approach to delineate capture zones and groundwater contribution areas was expanded.